Effects of H2O and CO2 on Electrochemical Behaviors of BSCF Cathode for Proton Conducting IT-SOFC. Issue 2 (14th December 2016) - Sun, Shichen; Cheng, Zhe
Abstract : Proton conducting intermediate temperature (400–700°C) solid oxide fuel cells (IT-SOFC) have attracted great interest recently. However, for SOFC operation at intermediate temperature, cathode is often considered to be the main factor limiting the overall cell performance. In this study, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF), which is one of the most active cathode materials and shows significant hydration effect suggesting possible proton conductivity, was investigated as the cathode for proton conducting IT-SOFC at temperature down to ∼450°C. The stability and compatibility of BSCF cathode with BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3-δ (BZCYYb), one of the leading proton conducting electrolyte materials, were studied at intermediate temperature in various atmospheres. In addition, experiments were carried out to understand the electrochemical behaviors of BSCF as a mixed proton, oxide ion and electron conducting cathode using BSCF/BZCYYb/BSCF symmetrical cells in simulated air containing different concentrations of water vapor (H2 O) and carbon dioxide (CO2 ), especially at lower temperature of ∼450°C. The results are analyzed from the underlying oxygen electrode reaction mechanism point of view, and the direction for future research to further improve the cathode for proton conducting IT-SOFC is pointed out.